Enhanced Cl2 sensitivity of cobalt-phthalocyanine film by utilizing a porous nanostructured surface fabricated on glass. Issue 7 (13th January 2017) - Kumar, Arvind; Samanta, Soumen; Latha, S.; Debnath, A. K.; Singh, Ajay; Muthe, K. P.; Barshilia, Harish C.
Abstract : We demonstrate a very simple and effective approach to improve the sensitivity and the low detection limit of cobalt phthalocyanine films towards the detection of chlorine by creating a porous nanostructured surface on a glass substrate via a vapor phase etching process. Abstract : In this paper, we demonstrate a very simple and effective approach to improve the sensitivity and the low detection limit of cobalt phthalocyanine (CoPc) films towards the detection of chlorine by creating a porous nanostructured surface on a glass substrate via a vapor phase etching process. CoPc films grown on etched glass (CoPc-etched films) exhibited entirely different morphology as compared to CoPc films grown on plain glass (CoPc-plain films). For 60 nm thickness, randomly distributed CoPc nanostructures were grown on the etched surface, whereas the CoPc-plain film showed an elongated granular structure. For 250 ppb Cl2 exposure, the CoPc-etched film showed a response of ∼105%, which is ∼5 times higher than the CoPc-plain film (20%). In addition, it can detect Cl2 down to 100 ppb concentration; this low detection limit is superior to CoPc-plain film (250 ppb). The improved gas sensing property of CoPc-etched film is ascribed to the presence of more interaction sites for gas adsorption, which is confirmed by charge transport, X-ray photoelectron spectroscopy and Kelvin probe measurement. This novel approach of improving the sensitivity and low detection limit paves a new way for the application of surface etching in the gas sensing field of organic semiconductors.